Large-scale analytical water quality model coupled with GIS for simulation of point sourced pollutant discharges. (February 2015) - Fan, Fernando Mainardi; Fleischmann, Ayan Santos; Collischonn, Walter; Ames, Daniel P.; Rigo, Daniel
Abstract: Mathematical modeling is an important tool for water quality studies, and the integration of water quality models with geographic information systems (GIS) is very useful for information extraction and for results interpretation. In this context, this work presents the development of a water quality model coupled with GIS (MapWindow GIS) for representing impacts of point-sourced pollutants released with distinct durations under different flow scenarios, allowing a systemic view of the entire basin, and capable of being used with low data availability. The model is called SIAQUA-IPH and uses a pollutograph convolution scheme to represent multiple discharges and confluences in the basin, based on analytical solutions of the longitudinal advection-dispersion equation. Operational tests presented a full operational performance from all technical solutions adopted, and a representation of plumes considered satisfactory in comparison to observations. Additionally, a simple sensitivity analysis is presented, that gives useful insights about the model application. Highlights: Water quality decision support model fully coupled with an open GIS. Represents pollutants released with distinct durations using a convolution schema. Useful at low data availability and large scale basins, common on Brazilian cases. Results are compared with observed data and critically analyzed. Considerations are presented about the adopted modeling approach usage.